Preparation method of poly-o-phenylenediamine intercalated MnO2 positive electrode material and application of positive electrode material in aqueous zinc ion battery

The synthesis of PoPD-MnO2 positive electrode material with ammonium ions addresses the diffusion issues in zinc-ion batteries, improving conductivity and stability, leading to enhanced electrochemical performance and cost-effectiveness for zinc-ion batteries.

CN119725445AActive Publication Date: 2025-03-28ANHUI ZHONGRUI INFORMATION TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411886606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Zn2+ ions' high charge and radius, along with strong Coulomb interactions, lead to slow diffusion in existing electrode materials for zinc-ion batteries, causing material degradation and reduced electrochemical performance.

Method used

The development of a poly(4-phenylamine) intercalated manganese dioxide (PoPD-MnO2) positive electrode material, synthesized through a water-heating process with specific molar ratios of potassium permanganate and aniline, which introduces ammonium ions to enhance conductivity and structural stability.

Benefits of technology

This approach significantly improves the material's ionic conductivity, charge distribution, and zinc ion migration rates, enhancing cycle performance and safety while reducing internal resistance, with a cost-effective and environmentally friendly process suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725445A_ABST
    Figure CN119725445A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to a preparation method of a PoPD-MnO2 positive electrode material and application of the PoPD-MnO2 positive electrode material in an aqueous zinc ion battery. The preparation method comprises the following steps: dissolving potassium permanganate and o-phenylenediamine in deionized water, stirring at room temperature, transferring the fully mixed solution into a hydrothermal reaction kettle, carrying out hydrothermal reaction, cooling to room temperature, carrying out centrifugal cleaning, and carrying out vacuum drying to obtain the PoPD-MnO2 positive electrode material. According to the invention, ammonium ions are inserted into the electrode material, and the ammonium ions are inserted into MnO2, so that the interlayer spacing is enlarged, the active sites are increased, ion diffusion and charge transfer are effectively promoted, the conductivity of the material is improved, the internal resistance of the material is reduced, and the structural flexibility and stability of the material are maintained; therefore, the overall performance of the water-based zinc ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and specifically relates to a preparation method of a PoPD-MnO2 positive electrode material and an application thereof in an aqueous zinc ion battery. Background Art

[0002] With the rapid development of renewable energy such as solar energy, biomass energy, hydropower and wind energy, as well as the construction of smart grids, the development of microgrid technology and energy interconnection, energy storage technology is a new challenge that will change the global energy landscape. Electrochemical energy storage is highly valued due to its flexibility of application, high conversion efficiency and high power density, and is considered to be an important form of energy storage in the future. In the past decade, lithium-ion batteries have attracted widespread attention due to their high energy density and long cycle life. However, the further development of lithium-ion batteries is restricted by factors such as limited lithium resources, development difficulties, and potential safety issues in the use of high-cost organic electrolytes, which has led to the high cost of commercial lithium-ion batteries. In contrast, the reserves of zinc in the earth's crust are relatively abundant, about 3.5 times that of lithium reserves, and the mining technology is more mature. Therefore, among electrochemical energy storage systems other than lithium-ion batteries, aqueous zinc-ion batteries (AZIBs) have a higher theoretical capacity (820mAh·g -1 ), suitable redox potential, high abundance of zinc anode and non-toxic aqueous electrolyte are considered to be more promising battery research directions. In particular, the aqueous electrolyte used can provide higher ionic conductivity than organic electrolytes, thereby achieving better rate performance and better safety. Currently, many positive electrode materials have been applied to AZIBs, such as manganese oxides, vanadium oxides and Prussian blue analogs. However, Zn 2+ The high charge-to-ionic radius ratio and strong Coulomb interaction result in slow diffusion in the lattice of these electrode materials. 2+ The repeated insertion may cause the collapse and dissolution of the cathode materials, thereby degrading their electrochemical performance. Summary of the invention

[0003] To solve the above problems, the present invention provides a method for preparing a PoPD-MnO2 positive electrode material and application thereof in an aqueous zinc ion battery.

[0004] The technical solution adopted by the present invention is: a poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2, the preparation method of which comprises the following steps:

[0005] Weigh a certain amount of potassium permanganate and o-phenylenediamine and dissolve them in deionized water. Stir them at room temperature to fully mix them. Transfer the fully mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction. Cool to room temperature, centrifuge and wash to remove residual reactants, and vacuum dry to obtain PoPD-MnO2 positive electrode material.

[0006] The above-mentioned poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 has a molar ratio of potassium permanganate:o-phenylenediamine = 4:0.15-0.25.

[0007] The above-mentioned poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 is adjusted to pH = 4 after stirring and mixing.

[0008] The above-mentioned poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2, the hydrothermal reaction conditions are: reacting at 200°C for 24 hours.

[0009] The application of the above-mentioned poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 in aqueous zinc ion batteries.

[0010] The above application method comprises the following steps:

[0011] 1) Preparation of positive electrode: After the MnO2 positive electrode material PoPD-MnO2 intercalated with poly-o-phenylenediamine is uniformly mixed with a binder and a conductive material, a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0012] 2) Preparation of negative electrode: A zinc sheet with a thickness of 0.1 mm to 0.2 mm and a purity of 99% to 99.99% was polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm;

[0013] 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and the electrolyte is 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate to obtain an aqueous zinc ion battery.

[0014] In the above application, in step 1), the binder is PVDF.

[0015] In the above application, in step 1), the conductive material is Super-p.

[0016] The beneficial effects of the present invention are:

[0017] 1. By introducing ammonium ions during the synthesis process, the conductivity and ion diffusion rate of the material are significantly improved, and the internal resistance is reduced.

[0018] 2. The introduction of ammonium ions expands the interlayer spacing of MnO2, changes the charge distribution, and increases the Zn 2+ The migration rate in the hybrid material is improved, thereby improving the specific capacity and rate performance of the material during the charge and discharge process.

[0019] 3. Ammonium ions are used as support within the interlayer, improving the stability of the material.

[0020] 4. It has the characteristics of low cost, environmental friendliness and high safety.

[0021] 5. It has the advantages of higher energy density and power density.

[0022] 6. The synthesis process and assembly process are simple, easy to operate and control, and suitable for continuous large-scale production.

[0023] 7. After modification, the capacity of the positive electrode material increased from 53mAh / g to 93mAh / g.

[0024] 8. The method of the present invention is also applicable to other metal oxide positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the XRD spectra of MnO2 and PoPD-MnO2 prepared in Example 1.

[0026] Figure 2 It is the cyclic voltammogram of MnO2 and PoPD-MnO2 prepared in Example 1.

[0027] Figure 3 It is the SEM spectrum of MnO2 and PoPD-MnO2 prepared in Example 1.

[0028] Figure 4 This is a diagram of the specific capacity of MnO2 and PoPD-MnO2 prepared in Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0030] Example 1 Preparation of MnO2 and PoPD-MnO2

[0031] (I) The preparation method of MnO2 is as follows:

[0032] Weigh 632 mg of potassium permanganate powder, dissolve it in deionized water, stir at room temperature to fully mix, transfer the fully mixed solution to a polytetrafluoroethylene-lined stainless steel hydrothermal reactor, perform hydrothermal reaction at 200°C for 24 hours, cool to room temperature, centrifuge to remove residual reactants, and vacuum dry to obtain MnO2 positive electrode material.

[0033] (II) The preparation method of PoPD-MnO2 is as follows:

[0034] Weigh 632 mg of potassium permanganate and 21.6 mg of o-phenylenediamine, dissolve them in deionized water, stir at room temperature, add HCl to adjust the pH of the solution to 4, continue stirring until fully mixed, transfer the fully mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, carry out hydrothermal reaction at 200°C for 24 hours, cool to room temperature, centrifuge to remove residual reactants, and vacuum dry to obtain PoPD-MnO2 positive electrode material.

[0035] (III) Detection

[0036] Figure 1 is the XRD spectra of MnO2 and PoPD-MnO2 prepared in this example. Figure 1 It can be seen that after PoPD intercalation, the XRD spectrum of the sample did not show obvious changes. The shift of individual peaks and the increase in peak width indicate that ammonium ions were successfully inserted into the layered MnO2. Figure 2 It is the cyclic voltammogram of MnO2 and PoPD-MnO2. Figure 2 It can be seen that the area enclosed by PoPD-MnO2 is significantly larger than that of pure MnO2, which indicates that the capacity of PoPD-MnO2 is greater than that of pure MnO2. Figure 3 This is the SEM spectrum of PoPD-MnO2. Figure 3 It can be seen that the prepared PoPD-MnO2 is a typical nanoflower-like structure. Figure 4 is the specific capacity diagram of MnO2 and PoPD-MnO2. Figure 4 It can be seen that the specific capacity and cycle stability of PoPD-MnO2 are much higher than those of pure MnO2.

[0037] Example 2 Preparation of PoPD-MnO2

[0038] Weigh 632 mg of potassium permanganate and 16.2 mg of o-phenylenediamine, dissolve them in deionized water, stir at room temperature, add HCl to adjust the pH of the solution to 4, continue stirring until fully mixed, transfer the fully mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, carry out hydrothermal reaction at 200°C for 24 hours, cool to room temperature, centrifuge to remove residual reactants, and vacuum dry to obtain PoPD-MnO2 positive electrode material.

[0039] Example 3 Preparation of PoPD-MnO2

[0040] Weigh 632 mg of potassium permanganate and 27 mg of o-phenylenediamine, dissolve them in deionized water, stir at room temperature, add HCl to adjust the pH of the solution to 4, continue stirring until fully mixed, transfer the fully mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, carry out hydrothermal reaction at 200°C for 24 hours, cool to room temperature, centrifuge to remove residual reactants, and vacuum dry to obtain PoPD-MnO2 positive electrode material.

[0041] Example 4 Preparation of negative electrode material

[0042] A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm for later use.

[0043] Example 5 Preparation of negative electrode material

[0044] A zinc sheet with a thickness of 0.2 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm for later use.

[0045] Example 6 Preparation of aqueous zinc ion battery

[0046] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 1 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0047] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0048] Example 7 Preparation of Aqueous Zinc Ion Battery

[0049] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 2 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0050] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0051] Example 8 Preparation of Aqueous Zinc Ion Battery

[0052] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 3 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0053] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 4 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0054] Example 9 Preparation of Aqueous Zinc Ion Battery

[0055] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 1 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0056] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0057] Example 10 Preparation of aqueous zinc ion battery

[0058] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 2 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0059] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0060] Example 11 Preparation of aqueous zinc ion battery

[0061] 1) Preparation of positive electrode: The PoPD-MnO2 positive electrode material prepared in Example 3 was mixed with PVDF and Super-p in a mass ratio of 8:1:1, and a small amount of NMP was added as a solvent. After mixing evenly, the mixture was directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material;

[0062] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate was selected as the electrolyte to obtain an aqueous zinc ion battery and perform electrochemical testing.

[0063] According to the six aqueous zinc ion batteries assembled in Examples 6 to 11, we obtained that Example 6 had the best electrochemical performance, with a current density of 3 A·g -1 The long cycle life reaches 2200 cycles, and the capacity retention rate is 90%. Figure 4 As shown), since the PoPD-MnO2 formed when the molar ratio of potassium permanganate: o-phenylenediamine is 4:0.2 in Example 6 has a larger interlayer distance than pure MnO2, provides more active sites, and is more conducive to the embedding and extraction of zinc ions, thereby improving its electrochemical performance.

Claims

1. A poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2, characterized in that: The preparation method thereof comprises the following steps: Weigh a certain amount of potassium permanganate and o-phenylenediamine and dissolve them in deionized water. Stir them at room temperature to fully mix them. Transfer the fully mixed solution to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene for hydrothermal reaction. Cool to room temperature, centrifuge and wash to remove residual reactants, and vacuum dry to obtain PoPD-MnO2 positive electrode material.

2. The poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 according to claim 1, characterized in that: In molar ratio, potassium permanganate: o-phenylenediamine = 4: 0.15~0.

25.

3. The poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 according to claim 1, characterized in that: The pH of the solution after stirring and mixing was adjusted to 4.

4. The poly-o-phenylenediamine intercalated MnO2 positive electrode material PoPD-MnO2 according to claim 1, characterized in that: The hydrothermal reaction conditions are: reaction at 200° C. for 24 hours.

5. Use of the poly(o-phenylenediamine) intercalated MnO2 positive electrode material PoPD-MnO2 according to any one of claims 1 to 4 in aqueous zinc ion batteries.

6. The use according to claim 5, characterized in that: The method comprises the following steps: 1) Preparation of positive electrode: After the MnO2 positive electrode material PoPD-MnO2 intercalated with poly-o-phenylenediamine is uniformly mixed with a binder and a conductive material, a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with PoPD-MnO2 material; 2) Preparation of negative electrode: A zinc sheet with a thickness of 0.1 mm to 0.2 mm and a purity of 99% to 99.99% was polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm; 3) The positive electrode sheet prepared in step 1) is used as the positive electrode, the negative electrode sheet prepared in step 2) is used as the negative electrode, and the electrolyte is 2M zinc trifluoromethanesulfonate + 0.1M manganese sulfate to obtain an aqueous zinc ion battery.

7. The use according to claim 6, characterized in that: In step 1), the binder is PVDF.

8. The use according to claim 6, characterized in that: In step 1), the conductive material is Super-p.

Citation Information

Patent Citations

  • Electrochemical cell, component thereof and method for manufacturing the same

    CN116783722A

  • Zinc ion battery positive electrode material with double active components and preparation method of zinc ion battery positive electrode material

    CN116936792A

  • Application of quinonamine polymer in aqueous ammonium ion battery electrode material

    CN118599078A